Integration of clinical research and medical care, slow but continuing effective future - Wandile, Pranali M. (International Journal of Clinical Trials, 2023)
The demarcation between research and medical practice appears partly blurred as they often coexist together while still having significant differences between them. The prospective complete merger still seems to have a bright future that could benefit humankind. The goal of medical practice is to provide the diagnosis, palliative or curative therapy, preventative therapy and the term "research" is recognized as a pursuit to investigate a hypothesis and pull conclusions to develop the theory or contribute to generalizable knowledge. A clinical trial is usually described as a clinical research study protocol with certain objectives and steps to accomplish those objectives. Integrating evidence-based medicine in medical practice requires combining patient-targeted treatment and research and overcoming all possible methodological, organizational, and cultural challenges while integrating the teaching healthcare system.